Effects of short-term hyperoxia on erythropoietin levels and microcirculation in critically Ill patients: a prospective observational pilot study - Donati, Abele (BMC Anesthesiol, 2017)
BACKGROUND: The normobaric oxygen paradox states that a short exposure to normobaric hyperoxia followed by rapid return to normoxia creates a condition of ‘relative hypoxia’ which stimulates erythropoietin (EPO) production. Alterations in glutathione and reactive oxygen species (ROS) may be involved in this process. We tested the effects of short-term hyperoxia on EPO levels and the microcirculation in critically ill patients. METHODS: In this prospective, observational study, 20 hemodynamically stable, mechanically ventilated patients with inspired oxygen concentration (FiO(2)) ≤0.5 and PaO(2)/FiO(2) ≥ 200 mmHg underwent a 2-hour exposure to hyperoxia (FiO(2) 1.0). A further 20 patients acted as controls. Serum EPO was measured at baseline, 24 h and 48 h. Serum glutathione (antioxidant) and ROS levels were assessed at baseline (t0), after 2 h of hyperoxia (t1) and 2 h after returning to their baseline FiO(2) (t2). The microvascular response to hyperoxia was assessed using sublingual sidestream dark field videomicroscopy and thenar near-infrared spectroscopy with a vascular occlusion test. RESULTS: EPO increased within 48 h in patients exposed to hyperoxia from 16.1 [7.4–20.2] to 22.9 [14.1–37.2] IU/L (p = 0.022). Serum ROS transiently increased at t1, and glutathione increased at t2. Early reductions in microvascular density and perfusion were seen during hyperoxia (perfused small vessel density: 85% [95% confidence interval 79–90] of baseline). The response after 2 h of hyperoxia exposure was heterogeneous. Microvascular perfusion/density normalized upon returning to baseline FiO(2). CONCLUSIONS: A two-hour exposure to hyperoxia in critically ill patients was associated with a slight increase in EPO levels within 48 h. Adequately controlled studies are needed to confirm the effect of short-term hyperoxia on erythropoiesis. TRIAL REGISTRATION: ClinicalTrials.gov (www.clinicaltrials.gov), NCT02481843, registered 15th June 2015, retrospectively registered